2016
DOI: 10.1063/1.4945100
|View full text |Cite
|
Sign up to set email alerts
|

Access to residual carrier concentration in ZnO nanowires by calibrated scanning spreading resistance microscopy

Abstract: Scanning spreading resistance microscopy (SSRM) was performed on non-intentionally doped (nid) ZnO nanowires (NWs) grown by metal-organic chemical vapor deposition in order to measure their residual carrier concentration. For this purpose, an SSRM calibration profile has been developed on homoepitaxial ZnO:Ga multilayer staircase structures grown by molecular beam epitaxy. The Ga density measured by SIMS varies in the 1.7 × 1017 cm−3 to 3 × 1020 cm−3 range. From measurements on such Ga doped multi-layers, a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Overall, it is well-known that ZnO NWs exhibit a high electrical conductivity and thus a high doping level, regardless of the growth method involved [ 28 ]. However, charge carrier density values spread over several decades from 10 17 cm −3 to 10 20 cm −3 [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The main reason is related to a large incorporation of residual impurities (i.e., Al, Ga, In, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Overall, it is well-known that ZnO NWs exhibit a high electrical conductivity and thus a high doping level, regardless of the growth method involved [ 28 ]. However, charge carrier density values spread over several decades from 10 17 cm −3 to 10 20 cm −3 [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The main reason is related to a large incorporation of residual impurities (i.e., Al, Ga, In, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The study's results also showed that SSRM can be well adapted for the dopant/carrier profiling in ZnO nanostructure [47]. Figure 2 shows the scan electron microscopy (SEM) image of the as-grown ZnO nanowires [47]. The synthesize of the ZnO nanowires using chemical vapor deposition system at 1000°C temperature were reported by Yadav et al [48].…”
Section: Zno Nanowires Devicesmentioning
confidence: 65%
“…The study's results showed that the residual carrier concentrations of ZnO nanowires were found to be between 10 18 and 3 x 10 18 cm -3 . The study's results also showed that SSRM can be well adapted for the dopant/carrier profiling in ZnO nanostructure [47]. Figure 2 shows the scan electron microscopy (SEM) image of the as-grown ZnO nanowires [47].…”
Section: Zno Nanowires Devicesmentioning
confidence: 78%
See 2 more Smart Citations